RNA therapeutics inactivate PCSK9 by inducing a unique intracellular retention form. (May 2015) - Rocha, Cristina S.J.; Wiklander, Oscar P.B.; Larsson, Lilian; Moreno, Pedro M.D.; Parini, Paolo; Lundin, Karin E.; Smith, C.I. Edvard
Abstract: Hypercholesterolemia is a medical condition often characterized by high levels of low-density lipoprotein cholesterol (LDL-C) in the blood. Despite the available therapies, not all patients show sufficient responses, especially those with very high levels of LDL-C or those with familial hypercholesterolemia. Regulation of plasma cholesterol levels is very complex and several proteins are involved (both receptors and enzymes). From these, the proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a promising pharmacologic target. The objective of this work is to develop a new approach to inactivate PCSK9 by splice-switching oligonucleotides (SSOs), converting the normal splice form to a natural, less abundant and inactive, splice variant. For this purpose, a new RNA therapeutic approach for hypercholesterolemia based on SSOs was developed for modulation of the splice pattern of human PCSK9 pre-mRNA. Our results show an increase of the selected splice form at both the mRNA and protein level when compared to non-treated Huh7 and HepG2 cell lines, with concomitant increase of the protein level of the low-density lipoprotein receptor (LDLR) demonstrating the specificity and efficiency of the system. In vivo, full conversion to the splice form was achieved in a reporter system when mice were treated with the specific oligonucleotide, thus further indicating the therapeutic potential of the approach. In conclusion, PCSK9 activity can be modulated by splice-switching through an RNA therapeutic approach. The tuning of the natural active to non-active isoforms represents a physiological way of regulating the cholesterol metabolism, by controlling the amount of LDL receptor available and the rate of LDL-cholesterol clearance. Highlights: Improved treatment options for hypercholesterolemia are unmet medical need. Here, we show that RNA therapeutics have the potential to modulate splicing of PCSK9. Consequently, levels of inactive intracellular PCSK9 splice variant are increased. As a biological proof of concept, LDLR protein levels are elevated. RNA therapeutics provide a promising treatment option for hypercholesterolemia.